The Decline of Lake Victoria Ferry Services in Kenya, 1961-2012 - Budi, Nashon Budy; Orondo, John Akumu; Okuro , Samwel; Odhiambo , George (Journal of Historical Studies, 2023)
Purpose: This study examined the operations of Lake Victoria Ferry Services since the independence of the East African countries in 1961 when the management was under the East Africa Railways and Harbors (EARH) and later the Kenya Railways Corporation (KRC). At the beginning of the 20th century the British colonial government established Lake Victoria transport as an extension of railway line in the lake region in Kenya and into Uganda. Despite some challenges, lake transport demonstrated progress in its services and expansion during the colonial period. However, when the management was transferred to the independent governments of East Africa, the operations of ferries were affected by the inefficiencies which marked the beginning of its decline. This study was guided by Politics of the Belly Theory of Bayart who associates underdevelopment of Africa long after independence with corrupt practices of African leaders. The theory shows that postcolonial African leaders have personalized the state for their own and their ethnic community's gain thereby neglecting the regions which are perceived to be opposing the ruling regime. Methodology: A Historical Research Design was used to conduct this study. Non probability sampling methods and procedures were used to identify informants during the collection of primary data. Other primary data were gathered from Kenya National Archives and Railways Museum in Nairobi. Secondary data was collected from relevant publications and other materials. Findings: The data obtained were analyzed using content and thematic analysis techniques. This study established that transition in management from colonial to independent East African governments, competition from road transport and disintegration of East African Community led to the decline of maritime transportation on Lake Victoria. In order to revive ferry services on the Lake, major rehabilitations on the existing ports must be done and modern ports built. In the same vein new transport vessels should be acquired. Finally, a permanent solution to the threat of water hyacinth must be pursued and regular dredging of navigational channels done regularly. Unique Contribution to Theory, Policy and Practice: This study suggests that, the government should promote integrated transport planning as well as developing proper regulations guiding Lake Victoria transport.